The social responsibility of international business scholars - Peng, Mike; Li Sun, S.; Blevins, D. (Emerald Group Publishing Ltd., 2011)
The paper aims to argue that the social responsibility of international business (IB) scholars is to seek truth, disseminate learning, and make a difference on issues crucial to the global economy. Instead of making philosophical and abstract arguments on the importance of the social responsibility of IB scholars, this article focuses on a leading debate of the times: How to view the rise of China's outward foreign direct investment (OFDI)? The article argues that the so-called “China threat” brought by such OFDI, as it is often portrayed by the (Western) media, is a myth that cannot be substantiated by evidence-based scholarly analysis. At present, China's OFDI stock represents a mere 1.21 percent of global OFDI stock. It would be absurd to believe that such a tiny sum can “buy up the world”. Based on findings, three hypotheses on what is behind the myth about China's OFDI are offered. Although some IB (and management) scholarships have been criticized for their alleged lack of relevance to practitioners and policymakers, this paper disagrees. IB scholars need to engage with issues of grave importance not only to the IB field but also to the wider world, such as China's OFDI. The article ends with a series of suggestions on how IB scholars, driven by social responsibility, can shed light on, clear the air, and steer the course of public perception, by drawing on time-honored, evidence-based scholarly tradition. To the best of the authors' knowledge, this is the first article in the literature on IB scholars' social responsibility.